Neutrophils launch monocyte extravasation by release of granule proteins - Soehnlein, Oliver; Zernecke, Alma; Weber, Christian (Thrombosis and Haemostasis, 2009)
During their journey from the blood stream to sites of inflammation polymorphonuclear leukocytes (PMN) release a wide panoply of granule proteins. Shortly after the PMN efflux, the extravasation of monocytes sets in and recent research provides evidence that the release of PMN granule proteins and monocyte extravasation are causally interrelated. Granule proteins seeded on the endothelium by adherent PMN allow direct activation and subsequent adhesion of monocytes. In addition, PMN granule components enhance the endothelial expression of cell adhesion molecules, efficiently supporting the arrest of monocytes at inflamed vessels. Moreover, granule proteins contribute to the fine tuning of the local chemokine network. Proteolytic modification of chemokines as well as enhancement of local chemokine synthesis lead to increased monocyte extravasation. Finally, PMN granule proteins exert direct chemotactic effects, a mechanism which is of special importance in the early recruitment of inflammatory monocytes. Hence, granule proteins modify the monocyte extravasation cascade in a multifaceted manner ensuring the efficiency of these mechanisms.
Keywords: Inflammation; neutrophil; monocyte; extravasation; chemokine